Comprehensive sexuality education as a primary prevention strategy for sexual violence perpetration - Schneider, Madeline (Trauma Violence Abuse, 2018)
Sexual violence (SV) represents a serious public health problem, with high rates (Smith et al., 2017) and numerous health consequences. Current primary prevention strategies to reduce SV perpetration have been shown to be largely ineffective – not surprisingly, since as others have pointed out (DeGue et al., 2014) current prevention largely fails to draw on existing knowledge about the characteristics of effective prevention (Nation et al., 2003). In this paper, we examine the potential of K-12 comprehensive sexuality education (CSE), guided by the National Sexuality Education Standards (NSES), to be an effective strategy. Our discussion uses socio-ecological and feminist theories as a guide, examines the extent to which NSES-guided CSE could both meet the qualities of effective prevention programs and mitigate the risk factors that are most implicated in perpetration behavior, and considers the potential limitations of this approach. We suggest that sequential, K-12 program has potential to prevent the emergence of risk factors associated with SV perpetration by starting prevention early on in the lifecourse. CSE has not yet been evaluated with SV perpetration behavior as an outcome, and this paper synthesizes what is known about drivers of SV perpetration and the potential impacts of CSE to argue for the importance of future research in this area. The primary recommendation is for longitudinal research to examine the impact of CSE on SV perpetration as well as on other sexual and reproductive health outcomes.